Invited Commentary: Just Using Computers for Any Subject is Not Enough to Acquire Computational Thinking in Early Childhood Education - Hermida, Maria Julia (2023)
Children around the globe are being raised in environments that are saturated with smart devices. Consequently, teaching computer science at schools is almost universally accepted, with most countries moving towards its inclusion in the curriculum, even as of kindergarten (Bers, 2019; Bers et al., 2019).One apparent reason for this educational decision is technology alphabetization: com-puting is a new literacy for the 21st century (Bers, 2019). Another reason is the change in the way of thinking about how to solve problems, that is, how we acquire computational thinking (CT). CT is defined as “... the thought processes involved in formulating problems and their solutions so that the solutions are represented in a form that can be effectively carried out by an information-processing agent” (Wing, 2011). CT includes at least four skills: a) breaking down a problem into easy steps; b) pattern recognition; c) abstraction; and d) the design of algorithms – understood as a series of steps to follow